A Nondestructive Islanding Detection Method Based on Adaptive and Periodic Disturbance on Reactive Power Output of Inverter-Based Distributed Generation - Xiaolong Chen (Journal of Applied Mathematics, 2014)
In order to detect islanding nondestructively, an islanding detection method for microgrid is proposed based on adaptive and periodic disturbance on the reactive power output of inverter-based distributed generation (DG). The first two parts of the disturbance in a cycle form a symmetric triangular shape and the disturbance can adaptively adjust its peak value and cycle time for two purposes. One is to minimize the total amount of the disturbance. The other is to guarantee that the absolute value of the rate of change of frequency (ROCOF) is constant during islanding, which can be utilized to be a criterion to detect islanding. The method can be applied on the DG either operating at a unity power factor or generating both active and reactive power simultaneously. Moreover, it helps to avoid the serious transient process during control strategy transformation of the DG for microgrid islanded operation. According to the anti-islanding test system in the IEEE Std. 929-2000 and IEEE Std. 1547-2003, several study cases are carried out in the PSCAD/EMTDC environment. The simulation results show that the proposed method can detect islanding rapidly and nondestructively. Moreover, it also performs effectively for the system with multiple DGs.